Theatrical Activity as a Means of Forming Soft Skills in Senior Preschoolers - Hladun, Lesia; Shyshak, Andriana; Rudenskyi, Rostyslav; Tirpák, Peter; Akimjak, Amantius; Moh’d Mansour, Ahmad (Journal of Education Culture and Society, 2025)
Thesis. The purpose of the study is to clarify the essence of the concept of ‘soft skills’ and determine the types that should be formed in senior preschoolers; to explain emotional intelligence and adaptability as one of the soft skills of senior preschool children, to specify their content; to substantiate the essence of theatrical activity and types of theatre in preschool education; to explain the use of theatrical activity for the formation of soft skills, in particular emotional intelligence and adaptability, in senior preschoolers. Concept. The relevance of the topic is related to the need for a personality of the XXI century to master a variety of soft skills, in particular emotional intelligence and adaptability. It is precisely in the preschool age when the foundations of these skills are formed, that theatrical activity has a significant potential for their development. Result and conclusion. The research reflects different approaches to the interpretation of the concept of ‘soft skills’ and the classification of this phenomenon. It defines the content of the terms ‘emotional intelligence’ and ‘adaptability’ as soft skills of senior preschool children. It is characterised by theatrical activity in preschool education institutions as a means of forming emotional intelligence and adaptability in senior preschoolers. The conclusion of the study emphasises the effectiveness of the use of theatrical activity for the development of soft skills of pupils of the senior group of preschool education institutions and reflects the variety of forms of its manifestation.